A single-center study of two types of upper kidney preservation surgery for complete duplicated kidney in children - Chu, Han; Zhang, Xian-sheng; Cao, Yong-sheng; Deng, Qi-fei (Frontiers in Pediatrics, 2022)
Objective The objectives of this study were to compare the efficacy, advantages, and disadvantages of insertable ureteral reimplantation (UC group) and ureteral end-to-side anastomosis (UU group) in the treatment of duplicated kidney and summarize the clinical experience in its diagnosis and treatment. Methods The current retrospective study enrolled 20 cases with duplicated kidney in Anhui Provincial Children's Hospital from April 2016 to June 2021, including 11 in the UC group and 9 in the UU group. There were 8 boys and 12 girls, with 12 on the left side and 8 on the right side. Meanwhile, there were three cases with urinary tract infection and nine with urinary incontinence. The rest of them were found by B ultrasound during physical examination. The median age of these patients was 33.5 months. Later, preoperative and postoperative renal pelvis separation, ureteral dilation, operation time, and drainage tube indwelling time were compared between the two groups. Results There were statistically significant differences in operation time (282 ± 50.55 vs. 176 ± 61.92, P = 0.03), drainage time (9.36 ± 5.00 vs. 5.33 ± 1.22, P = 0.02), and hospital stay (22.18 ± 5.40 vs. 14.78 ± 5.33, P = 0.007) between the two groups. In addition, the degree of hydronephrosis (UC: 1.86 ± 0.93 vs. 1.08 ± 0.77, P = 0.00; UU: 1.8 ± 0.95 vs. 0.89 ± 0.60, P = 0.02) and ureteral dilatation (UC: 1.57 ± 0.30 vs. 0.72 ± 0.22, P = 0.00; UU: 1.47 ± 0.50 vs. 0.88 ± 0.22, P = 0.001) were statistically different between the two groups before and after surgery. Conclusion Compared with the UC method, the UU method has the advantages of less trauma, faster recovery, and fewer complications. Double J tube or ureter stent placement is beneficial for finding and protecting the lower ureter intraoperatively, without increasing the difficulty in operation, which can also prevent anastomosis or ureteral orifice stenosis.